DEMENTIA: A REVIEW - Jamil, Mashal; Khan, Zarghuna; Zaman, Mashal; Amin, Laraib; Sadia, Haleema (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2022)
Dementia is any decline in cognition that is significant enough to interfere with independent, daily functioning. The aim of this review is to summarize the current findings in the field and address the important contributions of cerebrovascular, physiologic, and cellular alterations to cognitive impairment in these human dementias. Dementia is best characterized as a syndrome rather than as one particular disease. The causes of dementia constitute two broad categories of disease: those that are“neurodegenerative”(originally called "irreversible")and non-neurodegenerative (potentially "reversible"). Lastly. The treatment modalities of these dementias and their management is discussed.